Revolutionary Seminary and Human Sciences (Necessity and Actions for Change) - قاسم ترخان (سپهر سیاست, 2018)
Seminaries have been established with an aim to achieve philosophy of prophethood of the Prophets and to recognize, propagate and safeguard Islam and guidance of men and communities and finally, emergence of Islamic civilizations can regarded as their final goals. Since it is not possible to access to the afore-mentioned goals through secular human sciences, production of Islamic human sciences is considered to be among the first grade duties of seminaries. The present article has subjected attainment of the desirable human sciences to three actions taken by seminary and seminary scholars while it pays attention to a need for change in human sciences. These three actions are: a). Pathology and criticism of the prevalent human sciences; b). Production of necessary theoretical texts about the ideas of the Islamic human sciences; c). Attribution of religious doctrines and teachings to human sciences components and elements.